The racial hygiene explained to the chileans: the conferences of Otto Aichel (1927) and Erwin Baur (1930) in Santiago de Chile - Sánchez Delgado, Marcelo (Revista de Historia Social y de las Mentalidades, 2024)
This work deals with a particular moment of the transcontinental journey of ideas of German racial hygiene towards the Chilean context through the lectures by Otto Aichel -director of the Museum of Anthropology at the University of Kiel_ and Erwin Baur -a world-renowned figure in genetics of the first decades of the twentieth century- given in Santiago de Chile in 1927 and 1930 respectively. The thesis of the work is that, although they belong to the common root of the German racial hygiene, there are notable differences in the conferences because Aichel was born in Chile and had been a professor at the School of Medicine of the University of Chile, while Baur was a scientist in the vanguard of the genetics of the period. Methodologically the work offers a brief context of German racial hygiene to then compare the two conferences. In its results, the work identifies which are and what represent the differences between both conferences and ends raising some questions about the appropriation made by the chilean doctors, who could be felt reaffirmed in a thought prone to radical eugenics.
Keywords: Racial Hygiene; Erwin Baur; Otto Aichel; Eugenics